Balancing Social Media Reviews and Mass Media Coverage in Tourism Destination Image Building - Susanto, Eko; Sumarni, Sri (Integrasi Sains Media, 2025)
The image of a tourism destination plays a crucial role in attracting visitors and maintaining its competitiveness in the global market. This study examines the interaction between social media and mass media in shaping destination image, highlighting their complementary roles and the challenges in balancing their influence. Social media, characterized by its speed, interactivity, and user-generated content (UGC), provides early exposure to destinations, enabling rapid dissemination of information through viral campaigns, influencer promotions, and traveler reviews. However, it is often criticized for its lack of credibility, susceptibility to misinformation, and exaggerated portrayals. Conversely, mass media offers higher credibility and long-term influence through feature articles, expert testimonials, and structured storytelling, although it lacks social media's immediacy and engagement levels. This study employs a qualitative case study approach, utilizing content analysis of social media and mass media platforms and semi-structured interviews with 20 tourists and five destination managers. Findings indicate that 70% of tourists prefer social media for travel planning, as it provides real-time reviews and visually engaging content, while 30% rely on mass media for more credible and in-depth information. Destination managers adopt different strategies based on the type of tourism they promote; nature-based and urban destinations favor social media for rapid engagement, whereas cultural and historical destinations prioritize mass media for credibility and structured narratives. The Media Balance Model in Building Tourism Destination Image is proposed as a framework for integrating social media’s exposure and mass media’s credibility. The study underscores the importance of a holistic communication strategy, where social media is used for immediate attraction and engagement, while mass media reinforces long-term trust and reputation. As a practical implication, tourism stakeholders are advised to actively monitor online sentiment, manage crisis communication effectively, and collaborate with both media types to create a consistent and sustainable destination image.